2011
DOI: 10.1103/physrevlett.107.085501
|View full text |Cite
|
Sign up to set email alerts
|

Novel Self-Assembled Morphologies from Isotropic Interactions

Abstract: We present results from particle simulations with isotropic medium range interactions in two dimensions. At low temperature novel types of aggregated structures appear. We show that these structures can be explained by spontaneous symmetry breaking in analytic solutions to an adaptation of the spherical spin model. We predict the critical particle number where the symmetry breaking occurs and show that the resulting phase diagram agrees well with results from particle simulations.PACS numbers: 89.75. Kd, 75.10… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 23 publications
0
18
0
Order By: Relevance
“…One classic example of an inverse materials design problem is determining which isotropic pair potentials stabilize a specified ground state lattice. Previous studies addressing this type of problem found pair interactions that favor a wide variety of open two dimensional (e.g., square and honeycomb) [11][12][13][14] and three dimensional (e.g., diamond, wurtzite, and simple cubic) 15,16 target lattices, many of which readily assemble from the disordered fluid state upon cooling in a simulation. Interestingly, using stochastic optimization methods, Jain et al have demonstrated that these low-coordinated ground state structures can even be stabilized over a wide range of density by convex repulsive pair potentials [17][18][19] , qualitatively similar to the effective interactions 5 characteristic of soft gels, micelles, star polymers, etc.…”
Section: Introductionmentioning
confidence: 99%
“…One classic example of an inverse materials design problem is determining which isotropic pair potentials stabilize a specified ground state lattice. Previous studies addressing this type of problem found pair interactions that favor a wide variety of open two dimensional (e.g., square and honeycomb) [11][12][13][14] and three dimensional (e.g., diamond, wurtzite, and simple cubic) 15,16 target lattices, many of which readily assemble from the disordered fluid state upon cooling in a simulation. Interestingly, using stochastic optimization methods, Jain et al have demonstrated that these low-coordinated ground state structures can even be stabilized over a wide range of density by convex repulsive pair potentials [17][18][19] , qualitatively similar to the effective interactions 5 characteristic of soft gels, micelles, star polymers, etc.…”
Section: Introductionmentioning
confidence: 99%
“…One of the major goals in colloidal self-assembly is to devise new colloidal systems to self-assemble into lowdensity open crystalline structures [1][2][3][4][5][6][7], which are partially due to their promising applications in photonics [8], catalysis, porous media [9] and the special response to mechanical stress [10][11][12]. However, dated back to Maxwell, it has been proven that to maintain the mechanical stability, the coordination number of particles connected by central force bonds in periodic lattices must be larger than 2d in d dimensions [13].…”
Section: Introductionmentioning
confidence: 99%
“…Here, r is the distance between particle centers and θ are the parameters required for the pair potential. By minimizing either the ground state energy of the ideal configuration (relative to competing structures) or the free energy of an associated configurational ensemble at a higher temperature (relative to competing phases), researchers have successfully found isotropic interactions that stabilize a wide variety of structures and phases including, for example, two-dimensional honeycomb [40][41][42] and kagome [43][44][45] lattice assemblies as well as three-dimensional simple cubic 46 and diamond [46][47][48] crystals. Isotropic pair potentials that stabilize more exotic phases have also been discovered via recently introduced inverse design strategies [49][50][51] .…”
Section: Introductionmentioning
confidence: 99%